Fabrication of new ceramics nanocomposites for solar energy storage and release - Aseel Hadi; Ahmed Hashim Ah-yasari; Dalal Hassan (Institute of Advanced Engineering and Science, 2020)
The carbides nanostructures have huge applications in renewable energy fields such as the saving of solar energy and release which attributed to the good their properties (thermal, electrical, mechanical, optical and chemical). So, in this paper, the solar energy storage and release of carbides nanoparticles/water for building heating and cooling applications have been investigated with different concentrations of metals carbides nanoparticles (tantalum carbide-silicon carbide). The results showed that the melting and solidification times for thermal energy storage and release decrease with an increase (TaC-SiC) nanoparticles concentrations. From the obtained results, the TaC/SiC nanostructures/ water nano-system are considered as promising materials for solar energy storage and release with high efficiency and high gain (more than 50% compare with the water). Also, the TaC/SiC may be used for heating and cooling fields with good performance and high gain.